Configurational Analysis of Comprehensive Healthcare Quality: A Neutrosophic Set and fsQCA Approach - Jasson Humberto Ruiz Silva; Jasson Humberto Ruiz Silva; Manuel Richard Naranjo Rodríguez; Fatima Lissett Zambrano Coello (Neutrosophic Sets and Systems)
This study employs a nonlinear, neutrosophic approach to examine gaps in comprehensive healthcare by analyzing the interplay of Health Resource Availability (HRA), Professional Competence of Health Personnel (CPPS), and Accessibility and Response Time (ATR). Traditional statistical methods often fail to capture the uncertainty inherent in healthcare evaluations; this research addresses this by applying neutrosophic set theory to data from a survey of 15 professionals. fuzzy set qualitative comparative analysis (fsQCA) indicates that CPPS is a highly consistent (≈0.98) necessary condition for quality care, with HRA also being a strong necessary condition (≈0.89). As sufficient pathways, HRA individually (consistency ≈0.98, coverage ≈0.89), ATR individually (consistency ≈0.99, coverage ≈0.79), and combinations such as (HRA, CPPS) (consistency ≈0.99, coverage ≈0.86), alongside (HRA,CPPS,ATR), (HRA,ATR), and (CPPS,ATR) (all consistency ≈1.00), demonstrate robust routes to achieving quality care.This research contributes a nuanced understanding of healthcare system deficiencies by effectively managing indeterminacy. Findings suggest policies should enhance CPPS, ensure HRA, improve ATR, and foster their synergistic combinations to improve comprehensive healthcare quality. This work provides a foundation for future neutrosophic-based quality management in complex systems.